(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It is a paradox that inspite of rapid strides made in the field of science and technology, the economic problems have multiplied and have become more and more complex. In most developing countries, problems like poverty, unemployment and inequalities are still there.Gandhian approach to economic problems has its basis in Gandhiji‟s general philosophy which places premium on welfare of all. In the economic sphere, Gandhiji laid stress on self-sufficiency, fullemployment and decentralization of power etc,. Gandhian economic units have a degree of specialization according to the natural skill, talent, aptitude and capabilities of its inhabitants. His economic thinking thus lays stress on human resource use, village economy, rural industrialization, and decentralization, etc,. Growth does create some problems. But Gandhiji wanted that growth process should be a pleasant exercise. Mahatma Gandhi as a visionary of India, had a very clear perception of its villages and made an emphatic assertion that “India lives in her seven and half lakhs of villages‟. He further believed that India will have to live in villages, not in towns, in huts not in palaces. He held this conviction by saying that “If village perishes, India will perish too. Gandhi, played the leading role in securing for India political independence from the British Raj, through organizing and mobilizing Indian people from all walks of life in a peaceful and non-violent manner. He is therefore rightly called the „Father of the Nation‟. Gandhiji‟s approach to India‟s rural development was holistic and people-centred. It was rooted in his conviction in the tenets of truth, non-violence and the goodness of human-beings. Influenced as he was by Tolstoy, Ruskin and the teachings of the Gita, he placed more emphasis on moral and spiritual values than economic motives as a means of overall development.